(untitled) (Archive of Conferences, 2020)
An in-depth study of a major scientific source, such as Devonu lugati-t-turk, is important in revealing the potential of the Turkish language. The work is also of great importance for studying the lexical richness of the history of the Uzbek language. In this article, we will focus on the principle of interpretation of words in the Devonu lugati-t-turk.